One-year outcome of surgery compared with immobilization in a cast for adults with an undisplaced or minimally displaced scaphoid fracture: a meta-analysis of randomized controlled trials. (1st August 2022) - Johnson, Nick A.; Fairhurst, Caroline; Brealey, Stephen D.; Cook, Elizabeth; Stirling, Euan; Costa, Matt; Divall, Pip; Hodgson, Stephen; Rangan, Amar; Dias, Joseph J.
Abstract : Aims: There has been an increasing use of early operative fixation for scaphoid fractures, despite uncertain evidence. We conducted a meta-analysis to evaluate up-to-date evidence from randomized controlled trials (RCTs), comparing the effectiveness of the operative and nonoperative treatment of undisplaced and minimally displaced (≤ 2 mm displacement) scaphoid fractures. Methods: A systematic review of seven databases was performed from the dates of their inception until the end of March 2021 to identify eligible RCTs. Reference lists of the included studies were screened. No language restrictions were applied. The primary outcome was the patient-reported outcome measure of wrist function at 12 months after injury. A meta-analysis was performed for function, pain, range of motion, grip strength, and union. Complications were reported narratively. Results: Seven RCTs were included. There was no significant difference in function between the groups at 12 months (Hedges' g 0.15 (95% confidence interval -0.02 to 0.32); p = 0.082). The complication rate was higher in the operative group and involved more serious complications. Conclusion: We found no difference in functional outcome at 12 months for fractures of the waist of the scaphoid with ≤ 2 mm displacement treated operatively or nonoperatively. The complication rate was higher with operative treatment. Cite this article: Bone Joint J  2022;104-B(8):953–962.